Multicriteria Decision Making (MCDM) Methods for Ranking Estimation Techniques in Extreme Programming - Alshehri, S. (Engineering, Technology & Applied Science Research, 2018)
It is essential to use multicriteria decision making (MCDM) methods to evaluate human judgments, for decision problems requiring the measuring of tangible and intangible criteria. Among the MCDM techniques, the analytic hierarchical process (AHP) and its extended version, the analytic network process (ANP) are the most powerful methodologies for ranking options and alternatives. They have been utilized by many scientists and researchers in numerous fields, especially for complex engineering problems. Both tools allow leaders to structure their issues numerically utilizing individual judgments. In this article, it is suggested that the MCDM can be useful in agile processes where complicated decisions happen routinely. This paper shows the ranking of the extreme programming (XP) estimation methods using AHP and ANP in educational and industrial environments.